PERAN SOSIALISASI E-REGISTRATION TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS DI KPP PRATAMA SURABAYA WONOCOLO) - AINI, QURROTUL (Jurnal Akuntansi AKUNESA, 2013)
Directorate General of Taxation, as a manager of the tax system in Indonesia, are responsible for increasing tax revenues by implementing more modern tax system. Modernization of tax is done with simplification of the taxation process through IT, which called E-Registration, where the taxpayers do the registration and obtain the Taxpayer Identification Number (TIN) online. The impact of any number of changes in the tax laws required Directorate General of Taxation to socialize the taxation and help the Taxpayers to understand the latest tax regulations. The socialization of taxation is expected to increase the understanding and knowledge of taxation for all taxpayers and to build awareness to pay and report the taxes. If the confidence and awareness of the taxpayers to pay the taxes increases, the tax revenue will increase as well. Finally, national development will be faster  and the public welfare will be better. Key words : e-registration, modern tax system, Taxpayer Identification Number (TIN)